WAR CRIMES AND CRIMES AGAINST HUMANITY: GENERAL AND PARTICULAR IN THE DECISIONS OF INTERNATIONAL CRIMINAL TRIBUNALS AD HOC - R. Nevsky; N. Troitsky (Гуманитарные и юридические исследования)
The authors underline that the decisions of international criminal tribunals in Rwanda and the former Yugoslavia are valid for the domestic criminal law system. This is especially important; since it is in them that an official explanation of the essence of war crimes and crimes against humanity is given. However, in decisions of international ad hoc tribunals, acts that were similar in objective and subjective terms (murder, torture, acts of sexual violence and others) were qualified in some cases as war crimes, and in others as crimes against humanity. In accordance with applicable convention norms, the commission of acts of violence against prisoners of war and persons equated with them, as well as against prisoners during internal armed conflicts, should be regarded as a war crime. Therefore, the main problem in qualifying an offense as a crime against humanity or a war crime arises only if the victims are civilians. Based on the requirements of international criminal law and the decisions of international ad hoc tribunals, if a criminal act (when all «conventional» and «contextual» conditions are established) was committed against representatives of the civilian population during an armed conflict of international or non-international character or in direct connection with such conlict, it must be qualiied as a war crime. In accordance with conventional norms and general norms of international law, in order to qualify an offense as a crime against humanity, the context of «widespread» and/ or «systematic» attacks on the civilian population must be established. The position of the International Tribunal for the Former Yugoslavia that the attack on the civilian population does not have to be both large-scale and systematic is fundamentally important. This act can be qualiied as a crime against humanity if it meets at least one of these «contextual» conditions. In the decisions of the international ad hoc tribunals, one more principle has been developed for qualifying crimes against humanity: the involvement of the state in committing crimes against humanity (in the form of implementing a «plan» or «policy») is not a mandatory feature.